PEMBERIAN BILYET GIRO (BG) SEBAGAI BENTUK BOOKING TRANSFER DAN MASALAHNYA - Meily Oktavia Lingga (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT                       Giro generally used by businesses or entrepreneurs, because the  traffic of demand deposit payment was a practical and efficient also safer, because the giro using funds transfers from the publisher's account to the recipient's account giro. So publishing a giro also brought obligation for the issuer to provide funding in the form of current accounts. Publishers had an obligation to fulfill the little funds-at least essentially equal to the engagement. If the publishers did not have money in the bank, the bank would reject the giro. Sanctions against giro empty publishers, among others; For the first violation publishing vacant giro given the first warning letter, so that the concerned does not issue blank giro again; For violations of the issuance of the second blank giro given a second warning letter with the threat of closure of accounts and the inclusion of his name in the black list; For violation of issued empty Giro for third time, to customers directly notified by letter that gironya account is closed.          Efforts made by bank for issued empty giro: Fostering customer; rejected the giro which had not enough  funds ; By conducting clearing, this is to avoid the vacuum of funds in banks          Key Word : Giro, Bank , Empty Giro